Referral by pronoun and its impact on the consistency of the poetic text poem (the lyre of pain) Ibrahim Naji as a model (Journal of the College of Basic Education, 2023)
Summary of the research:Pronoun referral is one of the most important means of consistency of the text, because the pronoun is one of the most frequently used referential elements in speech, as it dispenses with it the repetition of nouns, in addition to the semantic function that it performs in the text, which is represented in clarifying its ambiguous connotations and linking its scattered sentences. This research is to demonstrate the effect of referral by pronoun on the consistency of the text in the poem (The Guitar of Pain) by the poet Ibrahim Naji, as it was built on a preface and two topics. for textual referral.